Nilai Etika Komunikasi dalam Relasi Ibu dan Anak pada Buku “Ibu, Aku Nggak Sekuat Itu” Karya Helobagas (Jurnal Riset Rumpun Ilmu Bahasa, 2026)
This study views literary works not only as entertainment but also as reflections of social life, particularly the relationship between mother and child. In the digital era, communication patterns within families have changed significantly. Therefore, communication ethics play an important role in maintaining emotional bonds and moral values between mothers and children so that relationships remain strong and well established. This study aims to describe and analyze the ethical values of communication and relationships in the novel Mother, I Am Not as Strong as It is by Helobagas. The research uses a qualitative descriptive method with documentation techniques, including reading, note-taking, and text analysis. The theoretical framework is based on Roslyn Frenz’s communication ethics theory, which includes five values: honesty, mutual understanding, well-being, confidentiality, and consequences. The results show that these five ethical values are clearly reflected in the novel’s dialogue and narrative. Honesty is shown through openness of feelings despite emotional pain; mutual understanding appears as a response to guilt; well-being is reflected in psychological care and protection; confidentiality functions to protect others’ feelings; and consequences demonstrate the long-term impact of communication patterns that may lead to emotional trauma in characters. This study concludes that communication ethics in families are not merely formal rules but also a form of emotional protection between parents and children.